Problematics of Thematic Learning at Grade II of Primary School - Dhora Alfarida; Amelia Putri Wahyuni; Miska Miska; Sri Orgeni; Suvina Mardhatillah; Nofriza Efendi (The Future of Education Journal, 2023)
The objectives of this study are: (1) identify problems of thematic learning preparation in grade II of elementary school; (2) identify problems of implementing thematic learning in grade II of elementary school; and (3) identify problems in thematic learning assessment in grade II elementary schools. The approach used in this study is descriptive qualitative. This type of research is a case study. This research data collection technique is in the form of observation, interviews, documentation to identify problems in thematic learning in grade II SDN 07 Ulak Karang Selatan. Referring to the results of the study, it was concluded that grade II teachers of SDN 07 Ulak Karang Selatan experienced problems in the preparation of thematic learning, the implementation of thematic learning, to the assessment of thematic learning. . Based on the conclusions of the study, it was suggested that the School and the Padang City Education Office hold trainings on thematic learning. In addition, grade II teachers must be guided by: thematic learning provisions, thematic syllabus, student development level and the environment around students.